Effect of Flux NH4F on Structure and Luminescence Properties of SrMoO4:Tb3+ Phosphors Synthesized by Microwave Radiation Method - Zhai, Yong-Qing; Li, Rui-Fang; Cui, Yao-Xuan; Song, Shan-Shan; Qiao, Jia (Asian Journal of Chemistry, 2014)
SrMoO4:Tb3+ green-emitting phosphors were prepared by microwave radiation method at medium-high power (560 W) for 0.5 h using active carbon as microwave absorbent and NH4F as the flux. The effect of flux NH4F on crystal structure, morphology and luminescent properties of samples were investigated by X-ray powder diffraction, scanning electron microscope and fluorescence spectrophotometer respectively. The results show that NH4F-added samples are Scheelite-type tetragonal phase SrMoO4 with space group I41/a. The particles of SrMoO4:Tb3+ phosphors prepared with flux NH4F have smooth surface and are larger than that of sample with no flux. With the increase of NH4F dosage, the location and shape of the excitation and emission spectra have no obvious change, but the luminescent intensity strongly depends on the dosage of NH4F. When the dosage of NH4F is 4 wt %, the emission intensity reaches to the maximum. Compared with the sample without flux, the intensity is enhanced about 58 %.